Concepções do sujeito-lírico em cantares de Hilda Hilst - Silva, Lívia Carolina Alves da (2009)
The present work accomplishes a systematic study about the composition of lyrical subject of Hilda Hilst in her work Cantares (2004). In order to develop this research, the methodology used was a combination of analysis and observation of the forementioned Hilst s book. Then some theoretical considerations were taken about who and how the subject is built in Hilst`s poems. By following Hilst s poetry one could face three relevant questions about her lyrical persona: the detection of a lyrical subject that recognizes himself as somebody constructed from his belonging to the other, out of him or as the self projected out of other self; the displacement of his identity by using a mask, and finally the ability of creating itself again, of thinking and constituting itself by means of the image and the word. Therefore this dissertation is organized in three chapters The being-beyond: the double face in Hilda Hilst s poetry , The self and the other behind the mask and The images and the word in Hilda Hilst s poetry in which the discussions proposed above are developed, revealing the building of a multiple and plural subjectivity.